The fetal sex ratio and metabolic, biochemical, haematological and clinical indicators of severity of hyperemesis gravidarum - Tan, P.C.; Jacob, R.; Quek, K.F.; Omar, S.Z. (Elsevier, 2006)
The association between female fetal sex and hyperemesis gravidarum is well established in European and North American populations. The association between female fetuses and severity of hyperemesis remains uncertain. A retrospective study based on case notes review of 166 Asian women hospitalised for hyperemesis was performed. Female fetuses were significantly associated with hyperemesis in our population (P = 0.004, OR 1.6, 95 CI 1.2-2.2) as well as associated with severe ketonuria and high urea. When both severe ketonuria and high urea were present at initial hospital admission for hyperemesis, 83 (95 CI 66-93) of the fetuses were female.